Pemanfaatan Mistar Gizi sebagai Media Pengukur Status Gizi untuk Meningkatkan Keterampilan Kader Dalam Menentukan Status Gizi Balita - Suaebah Suaebah; Jurianto Gambir (Poltekita : Jurnal Ilmu Kesehatan, 2020)
Nutritional status is a condition caused by a balance between the intake of nutrition from food and the need for nutrients by the body. Nutrition problems inthe community will effect the quality of human resources, so that it becomes a serious problems for future development. The purpose of this study was to find out the improvement of cadre’s skills in determining nutrtitional status by using the nutritionla bar design conducted on 45 caders subjects in Poyandu Lingga Village and Pancaroba Village, sungai Ambawang District Kubu Raya Regency, West Kalimantan.the results showed that the average skills of posyandu caders before being given training on the use nutritional ruler was 36.00 and after being given nutrition relur media increased to 95.22. Conclusion there are differences in the posyandu cader’s skill in using the nutrition bar to determine the nutritional status of children under five between before and after the nutrition bar is given (p=0,000).